ANALISA KALIBRASI ALAT PHOTOTHERAPY UNIT MENGGUNAKAN PHOTOTHERAPY RADIOMETER - Jesni Juwita Mendrofa; Yulizham Yulizham (JURNAL MUTIARA ELEKTROMEDIK, 2021)
Jaundice in newborns from January 2013 to December 2015, with a sample size of 223 babies. To treat jaundice in babies, Phototherapy is used. Phototherapy is the first action therapy for newborns with hyperbilirunemia. The provision of effective phototherapy is the main factor in the rapid management of hyperbilirubinemia.